2017
DOI: 10.1002/jcb.25659
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Role of Protandim and 6‐Gingerol in Protection Against Osteoarthritis

Abstract: Protandim and 6-gingerol, two potent nutraceuticals, have been shown to decrease free radicals production through enhancing endogenous antioxidant enzymes. In this study, we evaluated the effects of these products on the expression of different factors involved in osteoarthritis (OA) process. Human OA chondrocytes were treated with 1 ng/ml IL-1β in the presence or absence of protandim (0-10 μg/ml) or 6-gingerol (0-10 μM). OA was induced surgically in mice by destabilization of the medial meniscus (DMM). The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 35 publications
2
44
0
Order By: Relevance
“…5I). These results are in agreement with a recent report demonstrating that Nrf2 over-expression reduced the production of MMP-13 in IL-1β stimulated OA chondrocytes [48]. Collectively, these results demonstrate that Wogonin is a potent inducer of anabolic genes in OA chondrocytes in vitro and has the potential to suppress matrix degradation in vivo .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…5I). These results are in agreement with a recent report demonstrating that Nrf2 over-expression reduced the production of MMP-13 in IL-1β stimulated OA chondrocytes [48]. Collectively, these results demonstrate that Wogonin is a potent inducer of anabolic genes in OA chondrocytes in vitro and has the potential to suppress matrix degradation in vivo .…”
Section: Discussionsupporting
confidence: 93%
“…A recent study using nutraceuticals showed that protandim and 6-gingerol mediated Nrf2 activation offers protection against IL-1β-induced NO and PGE 2 production in OA chondrocytes [48]. Wogonin treatment of OA chondrocytes under stimulation with IL-1β completely inhibited the expression and production of varieties of inflammatory mediators including COX-2, PGE 2 , iNOS, NO, IL-6 and MMP-13 in human OA chondrocytes (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…As a consequence, inhibition of cell death is regarded as an attractive approach to control cardiac disease. It has been reported that 6 G exerts cellular protective effects against radiation-induced cell damage [29], 4-hydroxynonenalinduced cells mortality [19], amyloid-b-induced pheochromocytoma cells injury [30], and chlorpyrifos-induced oxidative damage in the brain, ovary and uterus [18]. The cyto-protection of 6 G has also been elucidated in hypoxia-induced injury [20].…”
Section: Discussionmentioning
confidence: 99%
“…6-Gingerol (6 G) is a natural chemical compound isolated from ginger (Zingiber officinale). Specifically, 6 G has been indicated to possess potential efficacies against tumour [11][12][13][14][15][16], oxidative stress and inflammation [17][18][19]. Moreover, potent protection of 6 G against hypoxia/reoxygenation-induced injury has been recently elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The chondroprotective effects of some antioxidant substances, such as gingerol and wogonin, have been demonstrated in human OA chondrocytes, through the activation of NRF2 signaling pathway [ 57 , 58 ]. No previous data was available regarding the effect of taurine on this transcription factor, so we showed for the first time a significant increase in NRF2 mRNA levels in the H 2 O 2 -stimulated chondrocyte cultures after treatment with taurine at a concentration of 200 μM.…”
Section: Discussionmentioning
confidence: 99%